Plant Extracellular Vesicles Contain Diverse Small RNA Species and Are Enriched in 10- to 17-Nucleotide "Tiny" RNAs. Issue 2 (31st January 2019) - Baldrich, Patricia; Rutter, Brian D.; Karimi, Hana Zand; Podicheti, Ram; Meyers, Blake C.; Innes, Roger W.
Abstract : The extracellular space of Arabidopsis leaves contains diverse small RNAs, both inside and outside of extracellular vesicles, with the former being enriched in 10- to 17-nucleotide–long "tiny" RNAs. Abstract: Small RNAs (sRNAs) that are 21 to 24 nucleotides (nt) in length are found in most eukaryotic organisms and regulate numerous biological functions, including transposon silencing, development, reproduction, and stress responses, typically via control of the stability and/or translation of target mRNAs. Major classes of sRNAs in plants include microRNAs (miRNAs) and small interfering RNAs (siRNAs); sRNAs are known to travel as a silencing signal from cell to cell, root to shoot, and even between host and pathogen. In mammals, sRNAs are transported inside extracellular vesicles (EVs), which are mobile membrane-bound compartments that participate in intercellular communication. In addition to sRNAs, EVs carry proteins, lipids, metabolites, and potentially other types of nucleic acids. Here we report that Arabidopsis ( Arabidopsis thaliana ) EVs also contain diverse species of sRNA. We found that specific miRNAs and siRNAs are preferentially loaded into plant EVs. We also report a previously overlooked class of "tiny RNAs" (10 to 17 nt) that are highly enriched in EVs. This RNA category of unknown function has a broad and very diverse genome origin and might correspond to degradation products.